Effectiveness Of Square Board Media for Quadratic Equations on Improving Student Learning on Quadratic Equations - In'am, Akhsanul; Umezurike John, Ezugwu; Eko Setiawan, Ruly (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
This study investigates the effectiveness of the square board as a teaching tool to improve students' learning outcomes in quadratic equations. This research is motivated by persistent global challenges in mathematics education, particularly regarding students' difficulties in understanding and solving quadratic equations due to their abstract and complex nature. The square board, which provides a visual and interactive approach, is designed to help students concretely visualize completing the square and the structure of quadratic equations. Using a quasi-experimental design, this study involved high school students divided into experimental and control groups. The experimental group received instruction using the square board, while the control group was taught using conventional methods. Data were collected through pre-tests and post-tests to measure conceptual understanding and problem-solving abilities. The results showed that students taught with the square board demonstrated significantly higher improvements in conceptual understanding and procedural fluency than those in the control group. These findings suggest that the square board increases engagement and motivation and addresses common misconceptions and procedural challenges associated with quadratic equations. This study contributes to the growing literature on innovative mathematics teaching methods by providing empirical evidence for using concrete manipulatives in algebra learning. This study also highlights the need for further research on integrating visual and interactive media in mathematics classrooms to support deeper learning and improve student learning outcomes.